Study of Medication Errors’ Types, Factors and Barriers from The Point of View of Nurses at Benghazi Medical Center - Lamya El Adouli; Basmah Nouri; Sarah Ahmed; Hana Abu Baker; Dania Mohamed (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. This study aimed to identify the most common types of medication errors and the most important factors that contribute to the occurrence of these errors. It also aimed to identify the main barriers to not reporting medication errors at the Benghazi Medical Center (BMC). Methods. The study used the descriptive approach, and the BMC was chosen randomly to be studied among the hospitals in the city of Benghazi. The study population consisted of all nurses working at the Benghazi Medical Center which were (332) nurses, and the response was (90%). The questionnaire was used as a study tool, and for data analysis, (SPSS) used statistical methods of percentages and frequencies. Results. From the nurses’ point of view, the most common type of error in (BMC) was "giving the dose at an unspecified time" (82.7%), and that the most important factors that contributed to medication errors were related to personal factors, namely too much pressure (78.3%), and the most factor related to the surrounding environment was the factor "being interrupted and distracted while working by another person" (75.0%). As for the factors related to poor communication due to writing, the most important factor contributing to the occurrence of error was the inability to read instructions due to poor doctor handwriting (73.0%). In addition, the main barrier to not reporting medication errors was the nurses’ uncertainty about what a medication error was (47.3%). Conclusion. Working on creating electronic systems that include detailed report forms for reporting errors and address all factors that negatively affect the work are worth.